Structure of social networks in the elderly people in poverty in the department of Quindío (Revista de Investigaciones Universidad del Quindío, 2010)
The purpose of this paper is to present the results of the research social networks of the population over 60years old in urban poverty in the department of Quindío that emphasizes the identification and analysis of the structure of social networks and life conditions presented by this population, in relation to their size; physical distance, social and psychological distance, frequency and types of contacts, and finally reciprocity. From these premises, it is possible to conclude that social networks of the poor elderly in urban settings play a determining role in relation to the support to the old people, both from the family and the unfamiliar network. The data show that a lot of them are receiving some help and are exceptional the cases where, having ties with family or friends and neighbors, the elderly get no support. This shows how the solidarity and mutual support replace or mitigate the lack of necessary resources that allow them access to goods and services they require to survive. This study confirms that women receive the most amount of support, but they also give so much support to formal and informal networks.
Keywords: Social network; structure of social networks; elderly people; oldage and poverty